Method for the development of WISH, a globally applicable index for healthy diets from sustainable food systems - Trijsburg, Laura; Talsma, Elise F.; Crispim, Sandra P.; Garrett, James; Kennedy, Gina; Vries, Jeanne H.M. de; Brouwer, Inge D. (MDPI, 2021)
Promoting both a healthy diet and at the same time considering the environmental sustainability aspects of production and consumption of the diet are urgent global issues. We developed the WISH (World Index for Sustainability and Health) to evaluate diets for healthiness and sustainability. The WISH seeks to measure two complex multidimensional concepts, diet quality and environmental sustainability, in one scoring system. The WISH is based on the EAT-Lancet recommendations for a healthy and sustainable diet in the general population with global applicability across multiple settings. Thirteen food groups are scored between 0 and 10, based on their association with disease and impact on environmental indicators. The scoring system was applied using a dataset of duplicate 24 h dietary recalls from 396 urban Vietnamese men and women. Out of a maximum score of 130, the mean total WISH score was 46 (SD 11), and scores for the healthy and high-environmental impact sub-scores were mean 25 (11) (out of 100) and mean 26 (8) (out of 70) respectively. A higher score was observed for the less-healthy (mean 20 (2) out of 30) sub-score. Our initial analysis shows that the WISH is able to differentiate between the healthiness and the environmental sustainability of a Vietnamese diet.